The Concept Of Ulul Albab According To M. Quraish Shihab In Tafsir Al-Mishbah QS. Ali Imran Verse 190-191 And Its Implication On Character Education - Yunita, Yunita; Awaluddin, Raisa Zuhra Salsabila; Al Muyassar, Faris (ZAD Al-Mufassirin, 2024)
The importance of this research is to examine the concept of ulul albab and its implications for character education. The research method used in this study is qualitative library type. The primary data source is Tafsir Quraish Shihab and the secondary data sources are books, articles, and proceedings. The data collection technique is documentation and the data analysis stage of this research uses content analysis techniques. The results in this study indicate that the implication of the concept of ulul albab in Tafsir Al-Mishbah Q.S Ali Imran Verse 190-191 is the role of reason as a remembrance in all circumstances and thinking with reason. Both of these activities will lead to knowledge in the human intellect. This will lead to the perfection of reason and spiritual intelligence. Spirituality education that is done correctly will make a person have an optimistic spirit, face life with a positive spirit, and see the world as a place to realize the common good. Thus, good spirituality will form a good character as well.